SHH pathway inhibition is protumourigenic in adamantinomatous craniopharyngioma - Carreno, G (Endocr Relat Cancer, 2019)
Pharmacological inhibition of the sonic hedgehog (SHH) pathway can be beneficial against certain cancers but detrimental in others. Adamantinomatous craniopharyngioma (ACP) is a relevant pituitary tumour, affecting children and adults, that is associated with high morbidity and increased mortality in long-term follow-up. We have previously demonstrated overactivation of the SHH pathway in both human and mouse ACP. Here, we show that this activation is ligand dependent and induced by the expression of SHH protein in a small proportion of tumour cells. We investigate the functional relevance of SHH signalling in ACP through MRI-guided preclinical studies using an ACP mouse model. Treatment with vismodegib, a clinically approved SHH pathway inhibitor, results in a significant reduction in median survival due to premature development of highly proliferative and vascularised undifferentiated tumours. Reinforcing the mouse data, SHH pathway inhibition in human ACP leads to a significant increase in tumour cell proliferation both ex vivo, in explant cultures, and in vivo, in a patient-derived xenograft model. Together, our results demonstrate a protumourigenic effect of vismodegib-mediated SHH pathway inhibition in ACP.